The Literature Study on Corrosion Rate in Mooring Chain for Tropical Seawaters – Class Rules Review - Hasan Ikhwani; Sista Mutya Atikanta; Wimala Lalitya Dhanistha (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2021)
Many design codes for structures in tropical waters are still based on the code for the North Sea, even though both have different environmental conditions. This research was conducted to assess the influence parameters of the tropical water environments and to determine the empirical estimates of the parameters that have a major effect on the corrosion that occurs in tropical waters. The result of this study will produce a practical equation function to estimate the corrosion loss based on the parameters of temperature, current velocity, and dissolve Nitrogen (DIN) for two different levels, low concentration level DIN, and high concentration level DIN. The function can analyze the estimation of corrosion that occurs in two different locations in the chain, the splash zone area, and immersed area. The corrosion rate (mm / year) obtained from the empirical estimation is then validated with the actual measurement data from the field obtained from the available literature. The empirical estimation results show a good fit when compared with data from existing actual measurements. Furthermore, the validated estimation results and actual data are compared with the existing class/code rules wear allowance. The corrosion rate results in particular conditions that exceed the corrosion wear allowances in the rules for data on tropical waters.